NKG2C+ memory‐like NK cells contribute to the control of HIV viremia during primary infection: Optiprim‐ANRS 147. Issue 7 (7th July 2017) - Gondois‐Rey, Françoise; Chéret, Antoine; Granjeaud, Samuel; Mallet, Françoise; Bidaut, Ghislain; Lécuroux, Camille; Ploquin, Mickaël; Müller‐Trutwin, Michaela; Rouzioux, Christine; Avettand‐Fenoël, Véronique; Moretta, Alessandro; Pialoux, Gilles; et al.
Abstract : Natural‐killer (NK) cells are important immune effectors during a viral infection. Latent CMV infection is widely spread and was demonstrated to shape the NK cell repertoire through the NKG2C receptor. An expansion of NKG2C + NK cells has been reported during primary HIV infection (PHI), but their role is not known. We previously found a correlation between the maturation state of the NK cell compartment and a lower viral load by studying patients from the ANRS 147 Optiprim trial. We investigated here extensively the NKG2C + NK cells at the time of PHI and its evolution after 3 months of early antiretroviral therapy (combination antiretroviral therapy (cART)). Multiparametric cytometry combined with bioinformatics was used to determine subsets. NK bright NKG2C + progenitor, NK dim NKG2C + effector and NK dim NKG2C + CD57 + memory‐like populations were identified. Two groups of patients were unraveled according to the distribution of the NKG2C + subsets skewed toward either progenitor/effector or memory‐like phenotype. Patients with high NKG2C + CD57 + NK cell frequencies showed lower HIV‐RNA, lower immune activation, higher pDC counts and reached more rapidly undetectable levels of HIV‐RNA at M1 under cART. NKG2C + CD57 + NK cell frequency was the only factor strongly correlated to low viral load among other clinical features. While the patients were cytomegalovirus (CMV) infected, there was no sign of reactivation of CMV during PHI suggesting that memory‐like NK cells were already present at the time of HIV infection and constituted a preexisting immune response able to contribute to natural control of HIV. This parameter appears to be a good candidate in the search of predictive markers to monitor HIV remission. HIV: Exposure to CMV offers partial immune protection: Prior infection with cytomegalovirus (CMV) leaves an immune footprint that helps contain HIV in patients undergoing antiretroviral therapy. A team led by Francoise Gondois‐Rey and Daniel Olive from Aix‐Marseille University, France, studied the white blood cells of 30 patients involved in a clinical trial testing drug cocktails for limiting HIV infection during the period following initial contact with the virus. The researchers measured levels of an infection‐fighting immune cell known as a natural killer cell that, in response to prior CMV exposure, expresses a particular surface receptor called NKG2C. They showed that patients with higher levels of these cells had some degree of pre‐existing immunity that helped limit HIV viral loads. Levels of this particular immune cell subset may provide a good predictive biomarker of who is likely to achieve HIV remission.